Effect of storage temperature on beneficial microbial load in rainbow trout feed supplemented with kefir - Ulukoy, G.; Kubilay, A.; Guzel-Seydim, Z.; Gumus, E.; Guney, S.; Kok-Tas, T.; Metin, S.; Diler, O. (Indian Journal of Fisheries, 2015)
Effect of different storage temperatures on beneficial microflora in rainbow trout feed supplemented with varying levels of kefir, produced using natural kefir grain was investigated. Three different feed samples were prepared using 2, 5 and 10% kefir supplementation into basal practical feed. Basal feed without kefir served as control. The feed samples prepared were stored in air-tight plastic bags at 24ºC, 4ºC and -20ºC for 28 days. Lactobacillus spp., Lactococcus spp., Lactobacillus acidophilus, Bifidobacterium spp. and yeast content of feeds stored at different temperatures were analysed on 1st, 7th, 14th, 21st, and 28th day of storage. Microbial counts in feed samples stored at 24ºC up to 28 days were found lower than those stored at 4ºC and -20ºC. Feed samples stored at 4ºC and -20ºC showed similar results pertaining to levels of microorganisms. Results showed that 5% kefir supplemented feed had the highest level of beneficial microbes which were able to survive at 4°C during 28 days of storage.